Effectiveness of Bobath Therapy vs. Conventional Medical Gymnastics in Psycho-Social and Cognitive Status Improvement in Children with Mild Neurodevelopmental Delay: A Randomized Double-Blinded Prospective Cohort Study - Zrinka Djukić Koroljević; Luka Bulić; Eva Brenner; Matea Bračić; Petar Brlek; Dragan Primorac (Biomedicines)
Background/Objectives: The main objective of this research was to compare the Bobath concept and conventional medical gymnastics in psycho-social and cognitive habilitation of infants with mild neurodevelopmental delay, and determine whether there is a difference in their effectiveness. Methods: The study included 100 children up to 3 months of age who were diagnosed with a mild neuromotor disorder based on clinical examination, the Münich Functional Developmental Diagnostic Test for the first year of life, and the Ages and Stages questionnaire. The respondents were randomized into two groups, habilitated according to the Bobath concept or conventional medical gymnastics. The observed parameters were problem-solving skills, communication skills, and the infants’ psycho-social status. Results: The Ages and Stages questionnaire revealed no significant differences between the two concepts. The Munich Diagnostic Test revealed different starting values in speech and socialization delay, but the treatment outcomes showed significant improvement in both cohorts. There were also no significant differences in the guardians’ opinions on therapeutic effectiveness. Conclusions: This study demonstrated that there is no difference in effectiveness between the two tested habilitation programs in mild neurodevelopmental delay treatment in infants after six months of therapy, laying the foundation for a professional consensus.